Seasonal variations in estradiol-17Î² and progesterone level during oestrus cycle in Malpura ewes - TAKARKHEDE, R C; HONMODE, J D; KADU, M S (The Indian Journal of Animal Sciences, 2014)
In cyclic ewes seasonal variation in estradiol- 17Î²Â and progesterone were studied. The highest estradiol-17Î² level was observed on day of oestrus, wherein declined on days 4, 8 and 12, and again sharply elevated on day 16. The E2 -17Î² levels on day 0 and 4 were significantly higher. The progesterone level on day of oestrus was lowest and showed significant elevation on days 4, 8 and 12. The level then declined on day 16. The progesterone levels on day of oestrus, 4 and 8 were significantly higher in summer than that in monsoon season. A highly significant negative correlation between E2-17Î² and progesterone levels was observed during estrous cycle. The E2: P4 ratio was narrowest on day 0 and later progressively widened on days 4,8 andÂ·1 2. On day 16 the ratio again reduced showing substantial reduction in progesterone and faster resumption of follicular activity.